Investigation of hydrodynamic performance of an OWC (oscillating water column) wave energy device using a fully nonlinear HOBEM (higher-order boundary element method). (1st April 2015) - Ning, De-Zhi; Shi, Jin; Zou, Qing-Ping; Teng, Bin
Abstract: Based on a time-domain HOBEM (higher-order boundary element method), a two-dimensional (2D) fully nonlinear NWF (numerical wave flume) is developed to investigate the hydrodynamic performance of a fixed OWC (oscillating water column) wave energy device. In the model, the incident wave is generated by the inner-domain sources to avoid the re-reflection at the inlet boundary. A self-adaptive Gauss integral method is introduced to tackle the mismatch between meshes on free surface and body surface. A simplified pneumatic model is used to determine the air pressure imposed on the free surface inside the chamber. The present model is validated against the published experimental and numerical results for OWCs over flat and sloping bottoms. Numerical model results indicate that the maximum air -pressure in the chamber does not occur at the same frequency as the maximum surface -elevation. For a fixed submerged depth of the OWC back wall, the peak efficiency increase with bottom slope initially then remains almost the same once the bottom slope reaches a certain value. The hydrodynamic efficiency attains a maximum value at a critical wave slope (wave slope kA i approximate 0.10 in the present study) and decrease from this value when the wave nonlinearity becomes either stronger or weaker. Highlights: A fully nonlinear numerical model for the hydrodynamic performance of a fixed OWC is developed. The frequencies of the maximum air-pressure and surface-elevation in the chamber are not same. Peak efficiency tends to a saturation status when the slope angle increases to a certain value. Hydrodynamic efficiency decreases from a critical value to both stronger and weaker wave slopes.